Perceptions and attitudes of teachers on visual impairment among elementary school students in Yogyakarta: A phenomenological study - Baswedan, Rizki Hafidzah; Damayanti, Laksmi; Ariasti, Nia; Nadya, Nurul; Muthi’ah, Niswah; Jamil, Nur Aisyah (Universitas Gadjah Mada, 2025)
Purpose: This study explored teachers' perceptions and attitudes toward visual impairments among elementary school students. Methods: A phenomenological approach was used in four elementary schools in Ngemplak, Yogyakarta. Twelve teachers were selected through purposive sampling. Data were collected using semi-structured interviews and analyzed manually using the Clarke and Braun thematic analysis method. Results: Teachers’ perceptions of visual impairment were primarily shaped by personal experiences and access to information, especially from the internet. Informants demonstrated knowledge about the causes, risk factors, and impacts of visual impairments, emphasizing gadget use and nutritional factors. Teachers commonly recognized signs of visual difficulty among students and implemented informal strategies such as seating adjustments and parent engagement. Most informants exhibited a positive attitude, expressing a willingness to collaborate with health services and emphasizing the need for regular vision screening and educational programs in schools. Conclusion: Elementary school teachers understand visual impairments well and approach students with visual difficulties positively. Enhancing teachers’ role in early detection and collaboration with healthcare services may improve school-based eye health programs.